Peran Kualitas Pelayanan dalam Meningkatkan Kepuasan Nasabah - Karnelis Karnelis; Alfath Isnaini (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the effect of service quality on customer satisfaction at PT Pegadaian Syariah Kuala Simpang Branch, Aceh Tamiang Regency. A quantitative approach with a causal associative research design was employed. The research sample consisted of 66 respondents selected using the Slovin formula and simple random sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using validity test, reliability test, simple linear regression, coefficient of determination, and t-test with the help of SPSS 29. The results indicate that service quality, which includes the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, has a positive and significant effect on customer satisfaction. Based on the regression equation Y = 8.421 + 0.781X, every one-unit increase in service quality will increase customer satisfaction by 0.781 units. The coefficient of determination value of 55.8% shows that the variation in customer satisfaction can be explained by service quality, while the remaining percentage is influenced by other factors. These findings confirm that improving service quality is a key strategy for maintaining and enhancing customer satisfaction and loyalty in Islamic financial institutions.